2012
DOI: 10.1038/onc.2012.444
|View full text |Cite
|
Sign up to set email alerts
|

Breast tumor-associated osteoblast-derived CXCL5 increases cancer progression by ERK/MSK1/Elk-1/Snail signaling pathway

Abstract: The skeleton is the most common metastatic site for breast cancer, with bone metastasis causing pain as well as risk of pathological fractures. Interaction between tumors and the bone microenvironment creates a vicious cycle that accelerates both bone destruction and cancer progression. This study is the first to analyze the soluble factors secreted by breast tumor-associated osteoblasts (TAOBs), which are responsible for promoting cancer progression. The addition of CXCL5 (chemokine (C-X-C motif) ligand 5), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 38 publications
(46 reference statements)
4
93
1
Order By: Relevance
“…Other studies have identified CXCL5 as a predictor for bone-metastatic prostate cancer (52), and in a breast cancer metastatic model it was shown that this cytokine is a factor secreted by tumor-associated osteoblasts to function as an inducer of epithelialto-mesenchymal transition and metastasis (53). Furthermore, in a model of rhabdomyosarcoma, it was demonstrated that antibody-mediated neutralization of CXCR2 (a receptor for CXCL5) enhanced anti-PD1 effectiveness by preventing the tumor infiltration of the CD11b + Ly6G hi suppressor cells (54).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified CXCL5 as a predictor for bone-metastatic prostate cancer (52), and in a breast cancer metastatic model it was shown that this cytokine is a factor secreted by tumor-associated osteoblasts to function as an inducer of epithelialto-mesenchymal transition and metastasis (53). Furthermore, in a model of rhabdomyosarcoma, it was demonstrated that antibody-mediated neutralization of CXCR2 (a receptor for CXCL5) enhanced anti-PD1 effectiveness by preventing the tumor infiltration of the CD11b + Ly6G hi suppressor cells (54).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the CXCL5 upregulation may reflect inclusion of macrophage RNA in the analyses, but it is also possible that CXCL5 also may play a role in ATC tumor biology. CXCL5 has recently been implicated in mediating cell proliferation, migration and invasion in colorectal cancer and is associated with metastasis and worse prognosis in gastric and breast cancer (36,37). Another novel, ATC-specific overexpressed gene encodes the disks large-associated protein 5 (DLGAP5), a component of the kinetochore responsible for stabilizing microtubules and the spindle apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…169 Metastatic cancer cells secrete factors that induce proinflammatory cytokines/chemokines in osteoblasts such as IL-6, IL-8, CCL2 and CXCL5. [170][171][172] One of the factors expressed by cancer cells in response to different stimuli such as TGFb is parathyroid hormone-related protein (PTHrP), which acts in a paracrine manner to induce CCL2, IL-6 and the soluble IL-6 receptor (sIL-6R) in osteoblasts. 159,[173][174][175] A recent study showed that PTHrP induces IL-6 and VEGF-A in osteoblasts to activate CD11b þ /Gr1 þ myeloid cells in the bone marrow and enhance angiogenesis, the expression of matrix remodeling proteases and prostate cancer growth in bone.…”
Section: Molecular Pathways Of Metastasis-promoting Inflammationmentioning
confidence: 99%